Strengthening Environmental Awareness in Children Through Drawing Activities - Jasjfi, Elda Franzia; Rianingrum, Cama Juli; Iskandar, Layla Nurina Kartika; Wiana, Amanda; Hidayatullah, Ahmad Syarif (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Pondok Yatim and Dhuafa Tomang are located on Jl. Gelong Baru No. 8, Tomang Village, Grogol Petamburan District, West Jakarta, is inhabited by 10 children aged 3-12 years. Currently, no special environmental awareness or art activities are carried out by the children at Pondok Yatim and Dhuafa Tomang. Even though they are interested in the environment and have free time to carry out various activities after formal school ends, one of which is drawing. For this reason, drawing training activities are carried out to increase awareness of the environment through Community Service activities by the Faculty of Art and Design,  Universitas Trisakti. This activity aims to help the children Pondok Yatim and Dhuafa Tomang foster. The activity targets are gaining knowledge about the environment, developing drawing skills, and developing creativity. The training was carried out using the participatory action research (PAR) method to obtain primary information from the target audience and to participate actively in implementing the training. The training results are children's drawings on environmental themes with various creative objects and interactions with the surrounding environment as a reflection of the environmental concerns of the children assisted by Pondok Yatim and Dhuafa Tomang. The training activities were carried out well according to the objectives of the training activities.